Impact of Land Cover Change on Erosion in the Suso Watershed - Wahyuni; Maryani Sempa (Program Studi Kehutanan Universitas Muslim Maros, 2026)
Land cover change is primarily caused by direct land use, which, if carried out without considering conservation measures, can lead to the degradation of watershed quality, resulting in increased sedimentation and erosion with low infiltration rates. This study aims to examine land cover changes, other factors influencing erosion, and the effect of land cover on erosion in the Suso Watershed in 2018 and 2023 using the Soil and Water Assessment Tool (SWAT) model. The study consists of three stages: 1) Analysis of land cover data for 2018 and 2023 to identify changes in land cover related to erosion hazard; 2) Analysis of other influencing factors such as slope, rainfall, and soil type; and 3) Erosion hazard modeling using SWAT. Land cover change in the Suso Watershed between 2018 and 2023 significantly affected erosion hazard levels. In 2018, the area was predominantly classified under moderate erosion hazard (60–180 tons/ha/year), while in 2023, it shifted to being dominated by the severe erosion hazard category (180–480 tons/ha/year). Other factors contributing significantly to erosion include steep slope conditions (>45%), high annual rainfall (2,700.50–2,759.06 mm in 2018), which increased to a very high category in 2023 (3,062.72–3,157.82 mm), and the predominance of inceptisol soil types. The conversion of forested land to non-forested land, along with other influencing factors, has contributed to the increase in erosion hazard levels in the Suso Watershed.